ZAMONAVIY BOSHQARUVDA RAHBAR PROFESSIONALIZMINING AYRIM XUSUSIYATLARI HAQIDA - Qadirov, Q.; Matnazarov, J.S. (SCIENCE and SOCIETY, 2022)
This article provides information on the specific features of the excellent leadership for the present day situation.
Keywords: leader; professionalism; education; intelligence; ability